Pelestarian Budaya Kerajinan Kendang Djimbe di Kelurahan Tanggung Kecamatan Kepanjenkidul Kota Blitar - Hikmah Riski Ramadania; Dwi Retnani Sinarwati; Suryanti Suryanti (Universitas Palangka Raya, 2025)
This study examines the efforts to preserve the Djimbe drum craft culture in Kepanjenkidul District, Blitar City. The objectives of this study are: To describe the efforts to preserve the djimbe drum craft culture in Kepanjenkidul District, Blitar City. This study is a descriptive qualitative study using observation, interview and documentation methods. Data analysis was carried out by data reduction, data presentation and drawing conclusions. By using the Chaeder Alwasilah theory study, this study examines how preservation efforts can be carried out. The results of the study indicate that the Djimbe Drum Craft Culture in Kepanjenkidul District has met three aspects, namely (1) Appreciation, Increasing Knowledge, in this aspect the Djimbe Drum Craft Culture has three indicators including cultural heritage, environment, availability of raw materials, understanding history, manufacturing process and empowerment through exhibitions and training. (2) Collective planning, in this aspect the Djimbe Drum Craft Culture has four indicators including increasing quality by maintaining value, developing marketing methods, developing innovation, and optimizing coordination with related parties. (3) Utilization of Cultural Productivity, in this aspect the Djimbe Kendang Craft Culture has five indicators which contain the impacts resulting from the Djimbe Kendang Craft Culture for the surrounding community and the City of Blitar.